Indução à Ovulação pelo Uso de LHRH Análogo e Fertilização Artificial em Rã-Touro (Rana catesbeiana) - Agostinho, Claudio Angelo [UNESP]; Wechsler, Francisco Stefano [UNESP]; De Oliveira Nictheroy, Paulo Eduardo [UNESP]; Pinheiro, Daniela Felipe [UNESP] (My University, 2000)
The objective of this study was to improve the artificial fertilization techniques for bullfrog, to increase the fertilization rate and become their use accessible for frog producers. Hormone dosages for inducing ovulation and spermiation followed those proposed by FALCON and CULLEY (1995) and ALONSO (1997); however, the artificial fertilization technique was adapted from the available methodology for artificial reproduction of fish with non-adhering eggs (WOYNAROVICH e HORVÁTH, 1983). The proposed technique consists of the following steps: I) synchronization of ovulation and spermiation through gonadotropin releasing hormone ((Des-Gli10, D-His(Bzl)6, Pro-NHEt9)-LHRH)); II) complete ovule extrusion in every female (1 to 2 minutes); III) ovule fertilization (2 minutes) with sperm diluted in 100 mL water; IV) ova hydration in 10-20 L water; V) ova incubation in screen frames, measuring 1,0 x 0,7 m, with 1 mm screen size. Fertilization rate obtained with the proposed modifications stayed above 60 %. It should also be emphasized that the proposed techniques allowed to obtain several spawns from the same frog, and each female was able to ovulate, approximately, every 45 days.
Spawning Inducing by Analog LHRH and Artificial Fertilization of Bullfrog (Rana catesbeiana)
Keywords: Artificial fertilization; Bullfrog; LHRH; Reproduction